Transthoracic Color Doppler Ultrasound-Guided Grooved Negative Pressure Drainage Tube Implantation in Pericardial Effusion After Cardiac Surgery - Can Feng; Zhengwen Lei; Peng Xiyang (Brazilian Journal of Cardiovascular Surgery, 2023)
ABSTRACT Introduction: Pericardial effusion is a common complication without a standard postoperative effusion treatment after cardiac surgery. The grooved negative pressure drainage tube has many advantages as the emerging alternative for drainage of pericardial effusion, such as it changes the structure of the traditional side hole, uses the capillary function to ensure drainage smooth, etc. The purpose of this study was to assess the feasibility and effectiveness of transthoracic color Doppler ultrasound-guided grooved negative pressure drainage tube implantation in pericardial effusion after cardiac surgery. Methods: All patients with pericardial effusion after cardiac surgery who underwent transthoracic color Doppler ultrasound-guided grooved negative pressure drainage tube implantation between January 2019 and December 2021 were retrospectively analyzed. Treatment results (including clinical symptoms, effusion volume, color Doppler ultrasonography, and computed tomography scan) were investigated to evaluate the effectiveness and safety of this method. Results: A total of 20 patients successfully underwent transthoracic color Doppler ultrasound-guided grooved negative pressure drainage tube implantation. After the operation, their symptoms (chest tightness, shortness of breath, etc.) were all relieved, and dark red or light red drainage fluid (> 200 ml) appeared in the newly placed drainage bottle. Color Doppler ultrasonography showed that the volume of pericardial effusion decreased significantly. Conclusion: The transthoracic color Doppler ultrasound-guided grooved negative pressure drainage tube is a safe and effective method for the treatment of postoperative pericardial effusion with less trauma, faster recovery, shorter in-hospital stay, and fewer complications.